Development of V-Shaped Beam on the Shock Resistance and Driving Frequency of Micro Quartz Tuning Forks Resonant Gyroscope - Bing Bai; Cun Li; Yulong Zhao (Micromachines, 2020)
The application of gyroscopes in harsh environments has always been a hot topic. As a high-quality material for manufacturing gyroscopes, quartz crystals need to be designed and optimized to meet the normal operation of gyroscopes in harsh environments. The Micro Electronics Mechanical System(MEMS) quartz tuning forks resonant gyroscope is one of the quartz gyroscopes. The elastic structure (V-shaped beam) between the anchor support point and tuning forks plays a vital role in the MEMS quartz tuning forks resonant gyroscope. This structure determines the natural frequency of the gyroscope, and more importantly, determines the shock resistance of the gyroscope structure. In this article, the MEMS quartz tuning forks gyroscope with different V-shaped beam thicknesses are simulated and analyzed by finite element analysis simulation software. After the modal analysis and shock simulation (the half-cycle sine shock pulse with amplitude of 1500 g (g is the acceleration of gravity) and duration of 2 ms in the six shock directions), the results show that when the beam thickness is 80 μm, the maximum stress is 94.721 MPa, which is less than the failure stress of quartz crystal. The gyroscope’s shock resistance is verified through shock testing.